2014
DOI: 10.1073/pnas.1401949111
|View full text |Cite
|
Sign up to set email alerts
|

Herbivore diet breadth mediates the cascading effects of carnivores in food webs

Abstract: Predicting the impact of carnivores on plants has challenged community and food web ecologists for decades. At the same time, the role of predators in the evolution of herbivore dietary specialization has been an unresolved issue in evolutionary ecology. Here, we integrate these perspectives by testing the role of herbivore diet breadth as a predictor of top-down effects of avian predators on herbivores and plants in a forest food web. Using experimental bird exclosures to study a complex community of trees, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
113
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(120 citation statements)
references
References 52 publications
4
113
1
Order By: Relevance
“…Besides differences in plant defence chemicals, it is also possible that 460 the two host plant species differ nutritionally, which can affect the performance of the larvae and 461 also their immunological defence (Singer et al 2014) 462 Overall, this study shows that P. plantaginis larvae are able to take up some amount of the …”
mentioning
confidence: 89%
“…Besides differences in plant defence chemicals, it is also possible that 460 the two host plant species differ nutritionally, which can affect the performance of the larvae and 461 also their immunological defence (Singer et al 2014) 462 Overall, this study shows that P. plantaginis larvae are able to take up some amount of the …”
mentioning
confidence: 89%
“…Several case studies found that larvae of specialist lepidoptera were better protected against predatory ants (Dyer 1995), paper wasps (Bernays 1988), and birds (Singer et al 2014) compared with generalist species. however, the cited papers consider both chemically defended and non-defended prey species.…”
Section: Variation Related To Prey Traitsmentioning
confidence: 99%
“…Host plant-specialized herbivores have either gained the ability to sequester plant-produced chemicals to defend themselves against attack by the third trophic level—often advertised through aposematic coloration—or they employ detoxification mechanisms and evasive strategies such as camouflage or mimicry (Farkas et al 2013; Petschenka and Agrawal 2016). Although the genomic consequences of these combinations of selection pressures are just starting to be explored (Joron et al 2011; Heliconius Genome Consortium 2012; Kunte et al 2014; Soria-Carrasco et al 2014; Zhan et al 2014), it seems probable that top-down forces, including generalist predators such as birds, are especially important (Bernays and Graham 1988; Singer et al 2014). …”
Section: Introduction: Insect Diversitymentioning
confidence: 99%